2017
DOI: 10.1055/s-0037-1605555
|View full text |Cite
|
Sign up to set email alerts
|

Shoulder Adhesive Capsulitis in Type 1 Diabetes Mellitus: A Cross-Sectional Study on 943 Cases in Sardinian People

Abstract: Purpose  To evaluate the prevalence of adhesive capsulitis (AC) of the shoulder in patients with type 1 diabetes mellitus (T1DM) in Sardinia. Methods  In this cross-sectional study, we evaluated 943 patients with T1DM attending the division of Endocrinology and Metabolism at the University Hospital in Sassari, Italy. The criteria for diagnosing AC were: pain for at least 1 month, inability to lie on the affected shoulder, and restricted active and passive shoulder joint movements in at least three planes. Age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 20 publications
(19 reference statements)
0
8
0
5
Order By: Relevance
“…Larkin et al defined frozen shoulder by self-report and shoulder flexion measurement and reported a prevalence of 31% of the patients [6]. A recent Sardinian study reported adhesive capsulitis in 35% of the patients [12]. Our findings highlight shoulder impairment in diabetes and stress the importance to find patients with shoulder immobility at an early stage to possibly prevent further deterioration of pain and stiffness [30].…”
Section: Discussionmentioning
confidence: 54%
See 2 more Smart Citations
“…Larkin et al defined frozen shoulder by self-report and shoulder flexion measurement and reported a prevalence of 31% of the patients [6]. A recent Sardinian study reported adhesive capsulitis in 35% of the patients [12]. Our findings highlight shoulder impairment in diabetes and stress the importance to find patients with shoulder immobility at an early stage to possibly prevent further deterioration of pain and stiffness [30].…”
Section: Discussionmentioning
confidence: 54%
“…In the clinical examination of the shoulder, 40% of the patients showed impaired mobility, "hands against back," which is compatible but not specific for frozen shoulder as well as the observed reduced mobility in several planes [4,22]. Previous reports regarding prevalence of frozen shoulder use somewhat different diagnose criteria [6,12,23] but involve pain, stiffness, and impaired shoulder range of motion. Numerous shoulder examination techniques have been evaluated in order to diagnose shoulder conditions; however, none of the tests is considered a 100% sensitive or specific [24][25][26][27][28][29].…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Adhesive capsulitis (Frozen shoulder) is a condition characterized by painful restriction in shoulder movement. Abduction and external rotation are mainly affected 44,45,63 . Frozen shoulder is a progressive condition, with a duration of 2-3 years.…”
Section: Upper Extremity Impairmentsmentioning
confidence: 99%
“…Four out of ten patients were unable to perform this test, followed by the "hands to roof" test (which 20% of the patients were unable to perform). The diagnostic criteria for frozen shoulder differs; however, the common denominators of frozen shoulder are pain, stiffness, and symptoms of impaired mobility 44,63,93 . Although a variety of shoulder examination techniques have been suggested for diagnostic testing, none shows perfect specificity or sensitivity [99][100][101][102] .…”
Section: Prevalence Of Ueis By Clinical Examinationmentioning
confidence: 99%